Η γλυοξάλη ως ρυπαντής στην ατμόσφαιρα:Βιβλιογραφική ανασκόπηση - Ελευθερίου, Αντώνης (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
The problem of air pollution and greenhouse gases in the atmosphere is a chapter of the atmospheric chemistry became highly concerned scientific community mainly in recent decades because of the serious impact caused to the environment and human health. Around the middle of last century, scientists began to study the accumulation of various gases in the layers of the atmosphere and contributing to a variety of processes and chemical reactions for the most part caused serious environmental problems. But then the lack of suitable equipment and existing technologies make the study of this problem in some cases impossible. But in recent years with the rapid development of technology and know-how scientists are able to identify and analyze the concentrations of these gases as well as their sources through satellite observation systems and measurement systems via terrestrial concentrations. The purpose of the present study thesis is the presentation of glyoxal (CHOCHO) and the study of the effects it has on the atmosphere and the reactions of the constituents of the atmosphere, in order to better understand the impacts caused by the emission of glyoxal in the atmosphere and the contribution to the problem of air pollution. This paper presents a series of experiments conducted by scientists to study the glyoxal. The first chapter presents the physicochemical properties of glyoxal as well as ways of manufacturing and production. Present various characteristics as the areas used in the industry and resulting from its use. The second chapter presents a series of experiments and surveys have been conducted to study the glyoxal in general. The use of Scanning Imaging Absorption Spectrometer for Atmospheric Cartography (SCIAMACHY) as a means of data collection and the use of computer models as TM4-ECPL and GEOS-CHEM used in experiments for observing the concentration of glyoxal and of substances produced by glyoxal the planet as well as to identify its sources. European Commission also conducted some experiments to determine whether the substance is dangerous to human health and not just the results of these experiments are discussed in this chapter. In the third chapter, the chemical reactions of glyoxal in the atmosphere as well as those which are considered precursors to the formation of glyoxal in the atmosphere as volatile organic compounds, aromatic hydrocarbons, in particular isoprene considered the most major precursor for the formation of glyoxal. This chapter also refers to the reactions of formation of secondary organic pollutants in the atmosphere with the contribution of glyoxal. In the fourth chapter, the protection and prevention of the effects caused by the emission of glyoxal in the atmosphere and especially the formation of secondary organic pollutants are presented. The main preventive and protective action to be taken is the reduction of the emission of precursor glyoxal formation in the atmosphere. Finally, the fifth chapter presents the conclusions drawn from this Diploma Thesis
Keywords: glyoxal; atmosphere